Impact of the testing protocol on the mechanical characterization of small diameter electrospun vascular grafts. (April 2020) - Stoiber, Martin; Grasl, Christian; Frieberger, Katharina; Moscato, Francesco; Bergmeister, Helga; Schima, Heinrich
Abstract: Aim: For the proper function of small diameter vascular grafts their mechanical properties are essential. A variety of testing methods and protocols exists to measure tensile strength, compliance and viscoelastic material behavior. In this study the impact of the measurement protocol in hoop tensile tests on the measured compliance and tensile strength was investigated. Methods: Vascular grafts made out of two different materials, a thermoplastic polyurethane (PUR) and polylactid acid (PLLA), with three different wall thicknesses were produced by electrospinning. Samples were tested with a measurement protocol that allowed the comparison of dynamic sample loading to a common quasistatic tensile test. Influence of measurement temperature, preconditioning cycles and the influence of a high number of loading cycles was also investigated. Compliance and tensile strength were evaluated and compared between the different samples and the different load cases. Results: In all samples a significant difference in the measured compliance was seen between an unloaded sample and a sample that was already in a preloaded state. For example in the PUR group with 100 μm wall thickness at 37 °C, the first compliance was 32.6 ± 9.6%/100 mmHg, which reduced to 15.4 ± 2.9%/100 mmHg at preloaded state. The PLLA group showed 7.5 ± 4.3%/100 mmHg vs. 0.94 ± 0.11%/100 mmHg respectively. The measurements showed the importance of dynamic testing, as the samples viscoelastic behavior had a considerable influence on the measured compliance. The quasistatic ultimate tensile test alone was not able to predict the sample's in vivo compliance. The measurement temperature had a significant influence on tensile strength and compliance. Both, the number of preconditioning cycles and the high number of loading cycles had a minor influence on the sample's compliance. Conclusion: With a quasistatic tensile tests alone, overestimated compliance values are measured in viscoelastic electrospun vascular samples, therefore dynamic loading cycles are required. Measurements at 37 °C are mandatory, as temperature has a significant influence on the mechanical properties. Graphical abstract: Image 1 Highlights: Impact of the measurement protocol on small diameter vascular grafts was investigated. Compliance and tensile strength were evaluated and compared between different samples. Different load cases caused significant differences in the measured compliance. At a previously unloaded sample a significant higher compliance was measured. The static tensile test alone was not able to predict the samples in-vivo compliance.